Archeologia śródmiejskich tajemnic Warszawy – nieznany żydowski dom studiów na Muranowie i pamiątki z powstania w 1943 r. - Konik, Jacek (Folia Praehistorica Posnaniensia, 2025)
Archaeology of Warsaw’s inner-city secrets – the unknown Jewish house of studies in Muranów and relics of the 1943 uprising Contemporary Warsaw consists of two cities: one visible on the surface, and the other hidden underground, destroyed during WWII. Archaeological excavations, that have been conducted in Warsaw in recent years, uncover secrets of the second city and remind us of its complicated history. One of such unique discoveries was a Jewish house of studies – bet ha-midrash. It was found in the ruined basement of a tenement house, preserved under the communal lawn for several decades, in the neighbourhood of the Jewish Combat Organization bunker at Miła street. The text discusses tradition of battei ha-midrash, and their existence in Warsaw of 19th and early 20th centuries. Artefacts found in the place in question, such as the remains of a burned Hebrew library, and the objects related to Jewish religious life, are also presented. These mementos of the murdered Jewish inhabitants of Warsaw are not only evidence of the era, but also they pose questions to the present generations. Is a modern, developing city able to take care of the reminders of the past? Can the community see the potential of memory?